Assessment of halal tayibban risks in broiler farming activities using the 'cause-and-effect diagram' approach - Ramli, Mohd Hasli; Rosman, Arieff Salleh; Md Sikin, Adi; Jamaludin, Mohammad Aizat (Human Resource Management Academic Research Society, 2024)
Generally, the supply of halal chicken meat is obtained through the process of slaughtering according to Islamic Shariah law and also by adhering to the procedures and standards developed by the authority JAKIM Malaysia. However, while the Halal Assurance Management System (HAMS) focuses on downstream stages like slaughter and processing, it neglects assessing halal risks in upstream farming activities. Therefore, the main objective of this study is to analyze the halal risk elements involved in chicken farming activities until the slaughter process is carried out. In this study, the Halal Tayyiban Risk assessment (HTR) is developed using the cause-and-effect diagram method, also known as the 'Fishbone diagram', which is considered a new approach in halal management. Thus, a qualitative methodological approach is adopted using document analysis methods such as journals, halal guidelines, and standards related to evaluates halal risks comprehensively. The results showed that there were seven HTR’s be identified which were during brooding phase, feed withdrawal, medication withdrawal, bird catching process, bird disposal, logistic activity and slaughterhouse. Furthermore, through the analysis of Cause-and-Effect diagram in this study, every element of halal risk not only outlines the potential halal risks but also elucidates the causal factors, enabling more effective mitigation measures to be taken. This assessment framework aids halal industry players in achieving halal compliance more effectively, with potential application in other farming sectors to supply halal meat products to Malaysia's Muslim community.